Kajian eksperimental kekuatan lentur dari perbaikan balok beton bertulang dengan metoda prepack, grout dan perkuatan baja pelat (strip). - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Magister Manajemen UGM, 2001)
A reinforced concrete beam was loaded under the concentrated statically monotonic load, then it was repaired by prepack method : loose concrete was removed and replaced with polymer concrete and cracks were filled by polymer injection. The repaired beam was tested by the same method as the original beam. Other beam, using grout and steel plate strengthening method was also performed. A comparison made among the four sets of data show improvement in the strength and stiffness of the repaired beams. The result show that failure beam repaired with polymer, improved the structural strength of beam capacity by 24.1 %, 13.1 % and 16.6 % compare to the last failure beam.